COCCUS BACTERIA IN FERMENTED DURIAN SPECIFIC FOOD OF BENGKULU - Hasanuddin Hasanuddin (Jurnal Agroindustri, 2017)
Coccus bactria is the cell of bacteria formed ball or ellip in 0,5 – 1µm diameter. Fermented durian is the fermented food prepared from spontaneous fermentation of durian (Durio zibethinus)with or without salt by wild bacteria. The sources of data in this study was laboratory analysis. Productions center of fermented durian, traditional markets were sampled for the experiment. Sampels were collected weekly in a month. Samples were analyzed microbiologically to determine and identify bacteria infermented durian. There were two species of coccus bacteria involved in fermented durian namely Pediococcus acidilacticiand Leuconostoc mesentroides. The specieseswere included in lactic acid bacteria.Lactic acid (C2H5COOH) is the organic acid that   can serve as a food preservation